Thalassemia Major in Punjab Pakistan, Epidemiology, Treatment Challenges, and Roadmap for Prevention. A Cross-sectional Observational Study - TANVEER, UMAR; ASGHAR, EJAZ; AZIZ, TASAWAR; SIENER, MAXIMILIAN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Thalassemia major is a severe hereditary blood disorder highly prevalent in Punjab, Pakistan, due to high consanguinity and limited screening programs. This study investigated its epidemiology, treatment challenges, and proposes preventive strategies to reduce disease burden. Aim of Study: To quantify the disease burden, healthcare challenges, and socioeconomic impact of thalassemia in Punjab, Pakistan, and propose evidence-based control strategies. Methodology: Current: Cross-sectional observational study was conducted from January 2022 to December 2023. Total 100 thalassemia major patients registered at DHQ Sahiwal’s Thalassemia Centre were enrolled. Data on demographics, clinical parameters, treatment adherence, complications, and family histories were collected via structured questionnaires and medical records. Blood samples were analyzed for ferritin levels and transfusion frequency. Results: Among 100 thalassemia major patients, 64% were diagnosed before age 2, and 78% had parental consanguinity. Only 58% received regular iron chelation therapy, and 21% had transfusion-transmitted infections. Financial burden was reported by 85% of families, while awareness of carrier screening and prenatal diagnosis was low (18% and 12%, respectively). Conclusion: Thalassemia major poses significant clinical and economic challenges in Punjab. Early diagnosis, inadequate treatment access, and poor preventive awareness highlight the urgent need for integrated screening, counseling, and support programs to reduce disease burden.